2021
DOI: 10.3389/fsufs.2021.659290
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Biodisinfection Effectiveness for Phytophthora capsici Control of Protected Sweet Pepper Crops in the Southeast of Spain

Abstract: Biodisinfection using fresh sheep manure in August is effective in controlling Phytophthora root rot in greenhouses in southeast Spain, but this is not the case after the beginning of September. The effectiveness of biodisinfection of new amendments has been evaluated beginning in October in sweet pepper greenhouses to control Phytophthora capsici. The amendments used were: T1: wheat husk + fresh sheep manure (FSM), 3.5 kg m−2; T2: sunflower pellets 3.5 kg m−2; T3: FSM: 3.5 kg m−2; T4: Control. Temperatures ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The sunflower pellets were also effective in reducing oospores viability of the phytopathogenic fungus Phytophthora capsici in biodisinfestation trials under sub-optimal temperature conditions in Southeastern Spain, and it was related with its ability to increase anoxia conditions during exposure to the biodisinfestation treatment [45]. In trials in pots and soil amended with compost made from olive oil mill waste, aubergine plants showed less prominent symptoms and slower disease development on account of Verticillium dahliae through biological control mechanisms [45,46]. Different studies, such as those by Etxeberria et al [47] and Lacasa et al [8] showed that above the threshold of 35 • C the presence of the pathogens Phytophthora capsici and Phytophthora nicotianae began to decrease considerably.…”
Section: Discussionmentioning
confidence: 99%
“…The sunflower pellets were also effective in reducing oospores viability of the phytopathogenic fungus Phytophthora capsici in biodisinfestation trials under sub-optimal temperature conditions in Southeastern Spain, and it was related with its ability to increase anoxia conditions during exposure to the biodisinfestation treatment [45]. In trials in pots and soil amended with compost made from olive oil mill waste, aubergine plants showed less prominent symptoms and slower disease development on account of Verticillium dahliae through biological control mechanisms [45,46]. Different studies, such as those by Etxeberria et al [47] and Lacasa et al [8] showed that above the threshold of 35 • C the presence of the pathogens Phytophthora capsici and Phytophthora nicotianae began to decrease considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability of Phytophthora to overcome the genetic resistance of plants owing to its genetic variability creates the need for alternative control methods for both diseases. Different cultivation techniques, such as grafting on resistant rootstocks [ 30 , 31 , 32 , 33 , 34 ] or nonchemical disinfection methods [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], have been used as alternatives. Crop rotation is a key component in the integrated management of diseases caused by Phytophthora ; nevertheless, the survival of oospores, even in the absence of hosts, limits the effectiveness of these methods [ 21 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address soil nutrient imbalances, crop productivity declines, and biodiversity losses [4], the South Korean government has devised long-term soil management action plans [5]. Some solutions suggested to address the challenges of continuous farming include crop rotation, soil solarization, and organic amendments [6,7].…”
Section: Introductionmentioning
confidence: 99%